Peran Pemimpin Gereja dan Etika Kristen dalam menyikapi Isu Kontemporer di Era Revolusi Industri 4.0 - Nova Ritonga (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2024)
Abstract: This article discusses the role of church leaders and Christian ethics in the era of the Fourth Industrial Revolution. Church leaders have a crucial responsibility in providing guidance and correct answers amidst the issues and challenges faced by the congregation and society. The literature review method was used in writing this article. The objective of this article is to explore the role of church leaders in addressing contemporary issues and upholding Christian ethics. The findings indicate that church leaders need to be sensitive and caring towards the congregation, and they play various roles such as administrators, organizers, decision-makers, group facilitators, board chairpersons, and counselors. The conclusion drawn is that church leaders must be able to provide guidance based on the Word of God and Christian ethics in dealing with complex issues in the era of the Fourth Industrial Revolution.Abstrak: Artikel ini membahas peran pemimpin gereja dan etika Kristen di era Revolusi Industri 4.0. Pemimpin gereja memiliki tanggung jawab penting dalam memberikan arahan dan jawaban yang benar di tengah persoalan dan isu yang dihadapi oleh jemaat dan masyarakat. Metode penelitian kepustakaan digunakan dalam penulisan artikel ini. Tujuan dari artikel ini adalah untuk menggali peran pemimpin gereja dalam menghadapi isu-isu kontemporer dan menegakkan etika Kristen. Hasil penelitian menunjukkan bahwa pemimpin gereja harus memiliki kepekaan dan kepedulian terhadap jemaat serta berperan sebagai administrator, organisator, pembuat keputusan, fasilitator kelompok, ketua dewan pengurus, dan konselor. Kesimpulan yang diperoleh, pemimpin gereja harus mampu memberikan arahan yang didasarkan pada firman Tuhan dan etika Kristen dalam menghadapi isu-isu yang kompleks di era Revolusi Industri 4.0